Low- and High-Tech Approaches to Control Plasmodium Parasite Transmission by Anopheles Mosquitoes - Chris M. Cirimotich; April M. Clayton; George Dimopoulos (Journal of Tropical Medicine)
Current efforts have proven inadequate to stop the transmission of Plasmodium parasites, and hence the spread of malaria, by Anopheles mosquitoes. Therefore, a novel arsenal of strategies for inhibiting Plasmodium infection of mosquitoes is urgently needed. In this paper, we summarize research on two approaches to malaria control, a low-tech strategy based on parasite inhibition by the mosquito's natural microflora, and a high-tech strategy using genetic modification of mosquitoes that renders them resistant to infection and discuss advantages and disadvantages for both approaches.